A Case of Renal Cortical Necrosis in a 15-year-old Boy with Acute Kidney Injury - Mi-ji Lee; Hyung Eun Yim; Kee Hwan Yoo (Korean Society of Pediatric Nephrology, 2019)
Renal cortical necrosis (RCN) is patchy or diffuse ischemic destruction of the renal cortex caused by significantly reduced renal arterial perfusion. It is a rare cause of acute kidney injury (AKI) and is associated with high mortality. Here, we review the case of RCN in a 15-year-old boy who developed AKI. A 15-year-old boy was referred to our hospital from a local hospital due to a sharp decrease in his renal function. He presented with acute flank pain, nausea with vomiting, and oliguria for the past two days. He had taken a single dose of antihistamine for nasal congestion. At our hospital, his peak blood pressure was 148/83 mmHg and he had a high body mass index of 32.9 kg/m2. The laboratory data showed a blood urea nitrogen (BUN) of 28.4 mg/dL, a creatinine of 4.26 mg/dL, and a glomerular filtration rate estimated from the serum cystatin C of 20.2 mL/min/1.73m2. Proteinuria (spot urine protein to creatinine ratio 1.66) with pyuria was observed. Kidney sonography showed parenchymal swelling and increased renal echogenicity. Due to rapidly progressing nephritis, steroid pulse therapy (750 mg/IV) was done on the second day of his admission and the patient showed complete recovery with normal renal function. However, the kidney biopsy findings revealed renal cortical hemorrhagic necrosis. Multifocal, relatively well-circumscribed, hemorrhagic necrotic areas (about 25%) were detected in the tubulointerstitium. Although RCN is an unusual cause of AKI, especially in children, pediatricians should consider the possibility of RCN when evaluating patients with rapidly decreasing renal function.